Criteria Based Case Review: The Parent Child Psychological Support Program - Pilar Bujia-Couso; Anita O'Rourke; M. Angeles Cerezo (Irish Journal of Applied Social Studies, 2010)
The Parent Child Psychological Support Program (PCPS) was established in an area of South West Dublin in 2001. Since then until May 2008 it has offered its services to over 700 children and their parents. This preventative, parenting support service is available to all parents of children aged 3 to 18 months within its catchment area. During periodical visits, the infant’s development and growth are measured and parents receive specific information about their child’s progress. Parents are empowered in their parenting practices, thus promoting consistency and synchrony in parent-child interaction. Between 2001 and 2006, 538 parents and their infants participated in the Program. Out of these cases, 130 (24.16%) were considered to require additional support and were included in the Monthly Meeting Case Review (MM) based on initial concerns The aims of this study were: 1. to review the first five years of MM cases and to explore the socio-demographic profile of the MM cases in comparison to those not in need of additional support (non-MM) and 2. To illustrate an approach to refining the case review process which will inform practice and provides the service providers with better understanding of the early detection of parent-child relation difficulties. In pursuing this goal the cases screened over five years of practice were analyzed to explore the structure of the different factors by using statistical techniques of data reduction, i.e. factor analysis. The results showed that the MM group differed on several socio-demographic dimensions from the non-MM group and there was a four factor structure underlying the case review decision process. Implications of this research are discussed.